Employees’ Views and Ethical, Legal, and Social Implications Assessment of Voluntary Workplace Genomic Testing - Sanghavi, Kunal; Feero, W. Gregory; Mathews, Debra J. H.; Prince, Anya E. R.; Price, Lori Lyn; Liu, Edison T.; Brothers, Kyle B.; Roberts, J. Scott; Lee, Charles (Frontiers in Genetics, 2021)
Employers have begun to offer voluntary workplace genomic testing (wGT) as part of employee wellness benefit programs, but few empirical studies have examined the ethical, legal, and social implications (ELSI) of wGT. To better understand employee perspectives on wGT, employees were surveyed at a large biomedical research institution. Survey respondents were presented with three hypothetical scenarios for accessing health-related genomic testing: via 1) their doctor; 2) their workplace; and 3) a commercial direct-to-consumer (DTC) genetic testing company. Overall, 594 employees (28%) responded to the survey. Respondents indicated a preference for genomic testing in the workplace setting (70%; 95% CI 66%-74%), followed by doctor’s office (54%; 95% CI 50%-58%), and DTC testing (20%; 95% CI 17%-24%). Prior to participating in wGT, respondents wanted to know about confidentiality of test results (79%), existence of relevant laws and policies (70%), and privacy protection (64%). Across scenarios, 92% of respondents preferred to view the test results with a genetic counselor. These preliminary results suggest that many employees are interested and even prefer genetic testing in the workplace and would prefer testing with support from genetic health professionals. Confirmation in more diverse employer settings will be needed to generalize such findings.